Effects of Xylanase in high-co-product diets on nutrient digestibility in finishing pigs - Asmus, M.D.; DeRouchey, Joel M.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
A total of 36 pigs (PIC 337 × 1050; initially 185 lb BW) were used in a 14-d study to evaluate the effects of xylanase (Porzyme 9302; Danisco Animal Nutrition, St. Louis, MO) in growing-finishing diets varying in dietary fiber on nutrient digestibility. Pigs were randomly allotted to 1 of 6 dietary treatments in a 2 × 3 factorial. Main effects were increasing dried distillers grains with solubles (DDGS; 35, 42.5, and 50%) with or without xylanase (0 or 4,000 units xylanase per kilogram of diet. The 6 treatment diets were corn-soybean meal–based with 15% added wheat middlings (midds), with 6 replications per treatment. All diets were fed in meal form. Multiple enzyme × DDGS interactive effects (P < 0.05) were observed for digestibility of various nutrients. The majority of these interactions resulted from differences in response to increasing DDGS with and without xylanase. In diets with xylanase, apparent digestibility generally decreased as DDGS increased. In diets without xylanase, apparent digestibility decreased as DDGS increased from 35 to 42.5% but increased in diets containing 50% DDGS. Overall, despite the interactions, increasing DDGS regardless of enzyme inclusion lowered (quadratic, P < 0.01) apparent fecal digestibility of DM, GE, ADF, NDF, and zinc as well as fecal digestibility (linear, P < 0.02) of fat, Ca, and P. Despite the interactions, adding dietary xylanase did not improve digestibility in corn-soybean meal–based diets containing fibrous co-products.
Keywords: Swine; DDGS; Digestibility; Enzyme; Fiber; Finishing pig